Numerical Investigation of Impact Characteristics of Rigid Retaining Wall for Blocking Landslides: A Case Study of the Shum Wan Road Landslide - Yunyun Fan; Feng Zhang; Ying Liu; Dongyang Ma (Geofluids)
Landslides pose a serious threat to the downstream infrastructure and personnel safety. For situations where the location of possible landslides is difficult to determine, or the potential landslides areas are widely distributed and scattered, passive protective structural measures need to be adopted to relieve the threat of landslides. Taking the Shum Wan Road landslide as an example, the discrete element method was used to reproduce and analyze the landslide movement. On this basis, this study conducts a further numerical investigation on the impact characteristics of the rigid retaining wall used to block landslides. The results show that the numerical back analysis can well represent the evolution of the landslide, and the numerical results are in good agreement with the actual situation, thus confirming its correctness and effectiveness. Under the condition of setting a rigid retaining wall, the landslide can be effectively blocked and form a final deposition behind the retaining wall. The impact on the rigid retaining wall varies with time, and the distribution of the impact in space is also uneven. Through the statistical analysis of the contact forces on the retaining wall, the distributions of static and peak stresses on the retaining wall can be obtained. Compared with the static stability, the spatial distribution of dynamic impact is more difficult to predict, especially the area of the peak impact has a significant influence on the design. Numerical investigation can efficiently and reliably provide abundant information of static stress and dynamic impact on the rigid retaining wall, which can provide important reference for the optimal design of the rigid retaining wall structure.